(untitled) (Al-Hasani: Journal of Islamic Studies, 2025)
With the development of technology and the internet, educators are required to be innovative, creatively fun and not boring in learning, one of which is by using quiz methods in learning that are assisted by quizizz game applications to evaluate learning and results. The Quizizz application is an online learning media with games, quizzes, discussions and surveys that make learning interesting and interactive, as well as helping teachers in evaluating and assessing students. Research used with a quantitative approach. The type of research used pre-experimental design with the design of one shot case study. The data collected in this study with tests assisted by the quizizz application. Dalam penelitian ini use data analysis techniques that terdir i dari test normality and continued by testing hypotheses that have been formulated toassist researchers in analyzing researchers’ data using JASP software. The results of the study there is a correlation between quizzes assisted by the quizizz game application in learning to understand the intrinsic elements of fabled fairy tales.